Intercultural Citizenship Education in Post-Conflict Contexts: The Case of Ethiopia - Ayana, Desta Kebede; Sercu, Lies; Mengistu, Demelash (African Journal of Education and Practice, 2025)
Purpose: In recent years, citizenship education has been the subject of much international attention, also in higher education. It is often called global citizenship, which includes a national and international dimension. By contrast, in some countries, especially those where high tensions between ethnic groups exist, citizenship education focuses primarily on preserving the country’s unity and the successful coexistence of multiple cultural, ethnic, and linguistic groups. Methodology: The study reported here considers the situation in Ethiopia, a super diverse country with 80 different ethnic groups and 109 languages spoken. Ethiopia is viewed as a post-conflict context, where the society has recently experienced a violent ethnic conflict that affected the daily lives of many citizens. The paper reports an interview study investigating how Ethiopian university administrators from two universities view citizenship education in higher education. Their views concern the need to promote intercultural competence as an important aspect of citizenship and ways to promote this competence as part of intercultural citizenship via curricular and extracurricular activities. Findings: The results show that universities avoid controversial issues or the highlighting of ethnicity, yet attempt to promote intercultural competence in their graduates via diverse approaches to intercultural citizenship education. Unique Contribution to Theory, Practice and Policy: We propose that the review and development of intercultural policies and practices are particularly timely because of the political and ethnocultural tensions still present in Ethiopian society.